Vulnerability and risk analysis of climate change Impacts on rice production (Oryza sativa L.) in Majalengka regency - Ruminta, Ruminta; Solihah, Linda Puspa; Wicaksono, Fiky Yulianto (Universitas Padjadjaran, 2024)
Climate change, especially temperature and rainfall shifting can be a threat to the agricultural sector, i.e., the decrease in rice yields in Majalengka Regency as the West Java rice production center. As an anticipatory measure to deal with that problem, a study is needed regarding the level of hazard, vulnerability and risk of climate change impacts in Majalengka Regency. This research aims to identify climate change and examine the level of hazzard, vulnerability and risk of the impact of climate change on rice production in each sub-district in Majalengka Regency. The method used in this research is descriptive quantitative. The data used in the analysis of the level of hazard, vulnerability and risk of climate change include temperature, rainfall, production, productivity, planting area, harvested area and farmers' socio-economic data obtained from Statistics Indonesia; Meteorology, Climatology, and Geophysical Agency; Agriculture Office of Majalengka Regency and other relevant sources, while farmer interview data were used in analyzing strategic adaptation options. The results of the study stated that areas with a very high potential risk of decreasing rice production (Risk Index or RI > 0.80) were in Kertajati District; the risk level of rice production in the high category (RI 0.61-0.80) was in Bantarujeg and Ligung Districts. Meanwhile, areas with a very high level of risk of decreasing rice productivity (IR) > 0.80) are in Bantarujeg District; high-risk level (IR 0.61-0.80) was in the Districts of Lemahsugih, Malausma, Argapura, Kertajati, Jatipuh and Ligung. The adaptation efforts that can be made to reduce the risk of decreasing rice production are the use of superior seeds, crop rotation, intermittent irrigation systems, acceleration of land preparation by mechanization, application of the jajar legowo cropping system, and integrated pest management measures.